(untitled) (Lectio: Journal of Language and Language Teaching, 2025)
The ritual of the peaceful banquet is one of the growing and still robust traditions, maintained in almost all areas in Lembata. In the east of Atadei, the ritual of a peaceful banquet known as ’begepen’. Odung is one of the clans in Atadei that is still maintaining the begepen ritual. Begepen is held in every ritual that involves all members of the clan. Begepen is a central ritual for family members when entering the clan’s house (una rayan). The ritual is held to gather all family members and their forefathers. Begepen is a family’s peaceful banquet based on a lovely sense and strong presence among the family members. In addition, this concept contains values described as similarity, brotherhood, openness and forgiveness. Begepen is a forefather heir tradition that improves each mistake, unites, and tightens the brotherhood among the clan members with their forefather. A form of brotherhood is once again an attempt to strengthen the identity of members of the Odung clan, particularly Indonesians. It indicates that the people in Atadei are still very strong in maintaining and performing the tradition that offers the values of courtesy as a national glorious culture.